A new zero temperature coefficient quartz oscillator plate - Ives, Walter Richard, Jr., author; Bottom, Virgil E., committee member; Frey, Paul Reheard, committee member; Olsen, Sterling Robertson, 1916-, committee member (Colorado State University. Libraries, 1951)
To view the abstract, please see the full text of the document. Abstract is at the end of the document, pages 78-89.
Keywords: Oscillators, Electric